Empowerment of MSMES in Increasing Competitiveness Based on Legality of Halal Businesses and Products - Farida, Nurul; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (Asian Journal of Management Analytics, 2024)
Business Licensing is the legality given to Business Actors to start and run their businesses and activities. having NIB speeds up the processing of other licenses because NIB is the initial requirement for obtaining various other documents, one of which is obtaining a halal certificate. Halal certificate is legal certainty of the halalness of a product. Halal products are products that have been declared halal in accordance with Islamic law. The purpose of this study was to determine the Empowerment of MSMES in Increasing Competitiveness Based on Business Legality and Halal Products. The results of this study indicate that the increase in small and medium enterprises cannot be separated from the role of the government in providing training and knowledge to improve the quality of products of business actors, one of which is in obtaining business licenses and halal product certificates. By having business legality and halal certificates business actors have a comparative advantage so that they are able to compete in the global market.